The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: modelling the clustering and halo occupation distribution of BOSS CMASS galaxies in the Final Data Release - Rodriguez-Torres, S. A.; Chuang, C. H.; Prada, F.; Guo, H.; Klypin, A.; Behroozi, P.; Hahn, C. H.; Comparat, J.; Yepes, G.; Montero-Dorta, A. D.; Brownstein, J. R.; Maraston, C.; et al. (My University, 2016)
We present a study of the clustering and halo occupation distribution of Baryon Oscillation Spectroscopic Survey (BOSS) CMASS galaxies in the redshift range 0.43 < z < 0.7 drawn from the Final SDSS-III Data Release. We compare the BOSS results with the predictions of a halo abundance matching (HAM) clustering model that assigns galaxies to dark matter haloes selected from the large BigMultiDark N-body simulation of a flat I > cold dark matter Planck cosmology. We compare the observational data with the simulated ones on a light cone constructed from 20 subsequent outputs of the simulation. Observational effects such as incompleteness, geometry, veto masks and fibre collisions are included in the model, which reproduces within 1 sigma errors the observed monopole of the two-point correlation function at all relevant scales: from the smallest scales, 0.5 h(-1) Mpc, up to scales beyond the baryon acoustic oscillation feature. This model also agrees remarkably well with the BOSS galaxy power spectrum (up to k similar to 1 h Mpc(-1)), and the three-point correlation function. The quadrupole of the correlation function presents some tensions with observations. We discuss possible causes that can explain this disagreement, including target selection effects. Overall, the standard HAM model describes remarkably well the clustering statistics of the CMASS sample. We compare the stellar-to-halo mass relation for the CMASS sample measured using weak lensing in the Canada-France-Hawaii Telescope Stripe 82 Survey with the prediction of our clustering model, and find a good agreement within 1 sigma. The BigMD-BOSS light cone including properties of BOSS galaxies and halo properties is made publicly available.
Citation: Rodriguez-Torres, S. A., Chuang, C. H., Prada, F., Guo, H., Klypin, A., Behroozi, P., . . . Thomas, D. (2016). The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: modelling the clustering and halo occupation distribution of BOSS CMASS galaxies in the Final Data Release. Monthly Notices of the Royal Astronomical Society, 460(2), 1173-1187. doi:10.1093/mnras/stw1014
Keywords: Methods: Numerical; Galaxies: Abundances; Galaxies: Haloes; Large-Scale; Structure Of Universe; Digital Sky Survey